PENGARUH AUDIT OPERASIONAL DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PELAYANAN KESEHATAN PADA RUMAH SAKIT UMUM FASTABIQ SEHAT PKU MUHAMMADIYAH PATI - Zumrotun Nafi’ah; Sri Wiranti Setiyanti (STIE Pelita Nusantara Semarang, 2018)
The hospital is a health institution engaged in the field of services that are required to create good health services in operational services. In creating good service, research is needed. This study aims to determine (1) the influence of Operational Audit on the Effectiveness of Health Services at the Hospital (2) the influence of Internal Control on the Effectiveness of Health Services at the Hospital (3) Pengauh Audit Operational and Internal Control on Health Services Effectiveness at the Hospital.The selected population is all employees at RSU Fastabiq Sehat PKU Muhammadiyah Pati which amounted to 200 people. Sampling technique using purposive sampling technique with sample amounted to 90 people. Variabe in this research is operational audit, internal control, and effectiveness of health service. Data collection techniques through questionnaires. Data analysis methods include analytical prerequisite test and hypothesis test. Prerequisite test analysis includes linearity test, multicollinearity test and heteroscedasticity test. Hypothesis test in this research using multiple regression analysis, coefficient of determination, partial test (t test) and simultaneous test (F test).Considering the multiple linear regression model, Y = 6,229 + 0,237X1 + 0,594 X2. The results of this study indicate that the Operational Audit and Internal Control there is a positive and significant influence on the Effectiveness of Health Services at the Hospital.Based on the results of the study, it is recommended that Fastabiq Health Hospital PKU Muhammadiyah Pati should add a good medical tool so that the services provided to be more effective. As well as Accounting and Management Information Systems owned by the hospital should be developed better again to improve internal control of the hospital, so as to improve the effectiveness of health services at the hospital.